Relationship Quality Between Stepdaughters and Stepfathers from the Children’s Perspective - Utami, Jemima Christian; Lentari, Fransisca Rosa Mira (Psychological Research on Urban Society, 2022)
Stepfather–stepdaughter relationship quality is linked to the child’s psychological well-being and stepfamily stability. However, there is still a lack of understanding of the dynamics of these relationships among sociodemographically diverse stepfamilies including families in different cultures. The aim of this research was to explore two Indonesian young women’s interpretations of the quality of their relationships with their stepfathers. The phenomenological study was conducted via interviews, and the women discussed their experiences in depth. The women’s perceptions of the quality of their connections with their stepfathers were primarily influenced by their stepfathers’ to build the relationships. The five dimensions of the theory of relationship quality were applied to assessing the women’s relationships with their stepfathers, and both women reported their relationships as largely negative, although one did have some positive memories. Suggestions are offered for future research that can expand on these findings, for instance through collecting data from all involved biological parents and stepparents.